Charlson comorbidity index (CCI) in diffuse large B-cell lymphoma: A new approach in a multicenter study - Eren, Rafet; Serin, İstemi; Atak, Süheyla; Pirdal, Betül Zehra; Nizam, Nihan; Gemici, Aliihsan; Aydın, Demet; Demirel, Naciye; Doğan, Esma Evrim; Yokuş, Osman (Springer, 2023)
Purpose: Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of adult lymphomas. The incidence of DLBCL increases with age and has a fairly rapid fatal course without treatment. Patients often have difficulty tolerating standard chemotherapy regimens due to their comorbidities. Charlson Comorbidity Index (CCI), which is calculated by considering 19 different comorbidities, was developed in 1987 and is widely used for mortality prediction in cancer patients. Literature data on CCI and hematological malignancies are limited. Main aim in this study is to evaluate the effectiveness of CCI and compare to the International Prognostic Index (IPI) scoring system in the DLBCL patient group. Methods: A total of 170 patients diagnosed with DLBCL between 1.1.2002- 1.12.2020 were included in the study. Statistical analyzes were performed among patients whose IPI and CCI scores were recorded by considering baseline data. Results: The median age of patients was 58 (range: 17–84). Thirty-five (20.6%) patients had stage III and 76 (44.7%) had stage IV disease. When the CCI, IPI and ECOG scores were compared with the mortality status of the patients as a reference, AUCs were resulted as 0.628 (95% CI: 0.506–0.749), 0.563 (95% CI: 0.484–0.639) and 0.672 (95% CI: 0.596–0.743), respectively. There was no significant difference between the ROC curves of CCI, IPI and ECOG scores. Patients with a CCI score of ? 4 had shorter OS comperad to those with a score of < 4. Conclusion: Rather than claiming that CCI is superior to IPI, ECOG or another scoring system in a single-center patient population, it should be stated that CCI is also an effective scoring system in patients diagnosed with DLBCL.
Keywords: Diffuse Large B-Cell Lymphoma; Charlson Comorbidity Index; Prognosis; Efficacy